Conscientização política e prática teórica no ensino de sociologia: um relato de experiência - Robson da Costa de Souza; Jefferson Evânio da Silva; Joanildo Burity (Ciências Sociais Unisinos)
This article will initially deal with the importance of Socio-Philosophical Studies in the context of high school teaching/learning processes, problematizing, from a broader discussion on school institutionalization, the epistemological and political issues involvedboth in the debate about the presence of disciplines such as Sociology and Philosophy in basic education as well as in the discussion on the use of methods and techniques for teaching sociological theories among students in the school system. Having as reference the experiences reported (and developed) in the scope of a discipline of Theories of Social Sciences offered by a Professional Master’s Degree, in the City of Recife (PE), we will then see how teaching sociology, in the school context, is related to the universe of research and knowledge production in Human Sciences, in general, and Social Sciences, in a specific way. Finally, we will bring the most general elements about a problematization of the challenges created by the recent curricular flexibilization in high school, regulated by Law nº 13.415 / 2017.